2018
DOI: 10.7717/peerj.4393
|View full text |Cite
|
Sign up to set email alerts
|

Underwater near-infrared spectroscopy can measure training adaptations in adolescent swimmers

Abstract: The development of an underwater near-infrared spectroscopy (uNIRS) device has enabled previously unattainable measurements of peripheral muscle hemodynamics and oxygenation to be taken within the natural aquatic environment. The purposes of this study were (i) to trial the use of uNIRS, in a real world training study, and (ii) to monitor the effects of a swim training program upon muscle oxygenation status in short distance swimming. A total of 14 junior club level swimmers completed a repeated swim sprint te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The heart blood volume during diastole in water is greater than that on land, therefore the stroke volume is increased, and the blood flow to the main action muscle group is increased 32,33 . Recent studies showed that more muscle oxygen utilization and muscle blood flow occur in water-based exercise than with land-based exercise, whether aerobic exercise, muscle exercise or aerobic combined strength courses 38,39 . The implication is that the oxygen and energy supplies are sufficient during muscle contraction in water, which can also accelerate energy metabolites elimination.…”
Section: Discussionmentioning
confidence: 99%
“…The heart blood volume during diastole in water is greater than that on land, therefore the stroke volume is increased, and the blood flow to the main action muscle group is increased 32,33 . Recent studies showed that more muscle oxygen utilization and muscle blood flow occur in water-based exercise than with land-based exercise, whether aerobic exercise, muscle exercise or aerobic combined strength courses 38,39 . The implication is that the oxygen and energy supplies are sufficient during muscle contraction in water, which can also accelerate energy metabolites elimination.…”
Section: Discussionmentioning
confidence: 99%
“…BLa, on its part, is sensitive to changes in exercise intensity and duration (Beneke et al, 2011 ). On the other hand, real-time data accumulation through NIRS is a useful evaluation tool during training efforts (Jones et al, 2018 ). Thus, the conjunction of the two testing procedures may prove beneficial for accurately and thoroughly evaluating intensity during swimming.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging that different responses, especially in high training efforts, have been shown during BLa and HR testing in swimming (Skorski et al, 2012 ), their usage in combination with near-infrared spectroscopy measurement can be realized as a form of alternative or complementary method, depending on the performed exercise intensity. Moreover, it may potentially offer a non-invasive analysis of dynamic changes in oxygenation and blood volume, detect the relative muscles contribution, and assess training-induced adaptations after endurance training (Jones and Cooper, 2016 ; Jones et al, 2018 ). Future studies should consider this relationship in swimming distances of longer duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using multiple NIRS sensors to different muscle groups, comparing local metabolic responses among each muscle toward the energy demand of the exercise is possible, and may help to diagnose weakness and strengths within a tailored training approach. Additionally, NIRS devices allow for the measurements in the applied settings as evidenced for a while in various challenging and even extreme sports such as speed skating (Hesford et al, 2013), swimming (Jones et al, 2018), and kayaking (Paquette et al, 2018(Paquette et al, -2020. In aquatic environments with a specially waterproofed NIRS device, Jones et al (2018) observed that improved oxidative metabolism of the muscle following 8-weeks endurance training in adolescents was strongly associated (not for HR and RPE) with the improved swim exercise performance.…”
Section: A Better Insight Of the Internal Training Loadmentioning
confidence: 99%